2021
DOI: 10.1002/er.6655
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and research of (Ni 0. 1 Co 0 . 3 Mn 0 .6 ) 3 O 4 as lithium‐ion battery conversion‐type anode using spen

Abstract: LiNi 1-x-y Co x Mn y O 2 lithium-ion battery, as the most installed battery of new energy vehicles, is facing the problem of large-scale scrap. In this paper, (Ni 0.1 Co 0.3 Mn 0.6 ) 3 O 4 anode material with a microsphere structure was successfully synthesized by carbonate coprecipitation method, which was obtained by recycling spent LiNi 0.6 Co 0.2 Mn 0.2 O 2 lithium-ion batteries through hydrometallurgy technology. This method eliminates the cumbersome separation steps, reduces the process cost, and realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Among the energy storage devices with wide applications, LIBs are an important candidates for highly effective energy storage system [ 12 24 ]. However, the current commercial graphite anode has the limitations, e.g., a relatively low theoretical capacity (372 mA h g −1 ), and some electrochemically active materials are proposed to be applied in LIBs [ 25 29 ]. In 2000, Poizot et al [ 30 ] reported that the transition metal oxides (TMOs) are considered as a kind of important anodes in LIBs since their high theoretical capacities 2–3 times that of graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Among the energy storage devices with wide applications, LIBs are an important candidates for highly effective energy storage system [ 12 24 ]. However, the current commercial graphite anode has the limitations, e.g., a relatively low theoretical capacity (372 mA h g −1 ), and some electrochemically active materials are proposed to be applied in LIBs [ 25 29 ]. In 2000, Poizot et al [ 30 ] reported that the transition metal oxides (TMOs) are considered as a kind of important anodes in LIBs since their high theoretical capacities 2–3 times that of graphite.…”
Section: Introductionmentioning
confidence: 99%
“…To replace the current intercalation-type electrode materials, a vast number of first-row transition metal oxides (TMOs) such as zinc oxide, nickel oxide, manganese oxide, copper oxide, cobalt oxide, and iron oxide are regarded as promising candidates. [7][8][9] Among these, spinel-type cobalt oxide (Co 3 O 4 ) possesses promising capacity values and retention. In the meantime, the spinel cobaltite (ACo 2 O 4 , where A = Fe, Mn, Zn, Cu, Ni, or Co) is also suitable for use as the anode in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…upon the delithiation or desodiation processes. [7][8][9][10][11][12][13][23][24][25] However, the estimated Gibbs free energies for the conversion reaction of TMOs with Na are more positive and thermodynamically less favorable when compared with those of Li. 26 Therefore, a comprehensive investigation is essential to determine the practicability of TMOs in SIBs.…”
Section: Introductionmentioning
confidence: 99%